2005
DOI: 10.1001/archinte.165.14.1643
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Response Syndrome After Acute Myocardial Infarction Complicated by Cardiogenic Shock

Abstract: Almost one fifth of patients with acute myocardial infarction complicated by CS showed clinical signs of severe systemic inflammation, and those who were culture-positive for sepsis had twice the risk of death. The observation of lower SVR at the onset of shock in patients who subsequently had culture-positive systemic inflammation suggests that inappropriate vasodilation may play an important role in the pathogenesis and persistence of shock and in the risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
150
0
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(174 citation statements)
references
References 22 publications
8
150
0
16
Order By: Relevance
“…In fact, sepsis was suspected in 18% of the SHOCK trial cohort, 74% of whom developed positive bacterial cultures. 29 SVR was lower in these patients, and low SVR preceded the clinical diagnosis of infection and culture positivity by days.…”
Section: Peripheral Vasculature Neurohormones and Inflammationmentioning
confidence: 74%
See 1 more Smart Citation
“…In fact, sepsis was suspected in 18% of the SHOCK trial cohort, 74% of whom developed positive bacterial cultures. 29 SVR was lower in these patients, and low SVR preceded the clinical diagnosis of infection and culture positivity by days.…”
Section: Peripheral Vasculature Neurohormones and Inflammationmentioning
confidence: 74%
“…The reflex mechanism of increased systemic vascular resistance (SVR) is not fully effective, as demonstrated by variable SVR, with median SVR during CS in the normal range despite vasopressor therapy in the SHOCK Trial. 29 In some patients, SVR may be low, similar to septic shock. In fact, sepsis was suspected in 18% of the SHOCK trial cohort, 74% of whom developed positive bacterial cultures.…”
Section: Peripheral Vasculature Neurohormones and Inflammationmentioning
confidence: 99%
“…MI вызывает развитие острофазного асепти-ческого воспалительного ответа, который в тяже-лых случаях приводит к системному воспалитель-ному ответу [14]. У больных с MI наблюдается многократное увеличение концентрации CRP, особенно выраженное у пациентов с ВО (табл.…”
Section: Discussionunclassified
“…[1][2][3][4] The current understanding of the underlying pathophysiology that marks patients with an unfavorable course and lack of response to treatment is limited. This was evident in the recently published Triumph trial that addressed the possible adverse effects of a presumed excessive nitric oxide (NO) production secondary to inflammation in CS.…”
mentioning
confidence: 99%
“…However, observational studies have suggested that systemic inflammation and neurohormonal activation plays an important role in the pathogenesis of CS. 3,[6][7][8][9][10] The naturally occurring NO-inhibitor asymmetrical dimethylarginine (ADMA) has been implicated in the pathogenesis of endothelial dysfunction and several chronic cardiovascular disorders. [11][12][13][14] In contrast to its increasing recognition as a risk marker in cardiovascular disease, little is known about ADMA's role in the acute setting.…”
mentioning
confidence: 99%